Global Trends and Knowledge Structure of Educational Transformational Leadership: A Scopus-Based Bibliometric Analysis from 2016 to 2026 - Diny Kristianty Wardany; Onwardono Rit Riyanto (MASI Mandiri Edukasi, 2026)
The increasing complexity of educational systems, driven by digital transformation, globalization, and sustainability demands, has made educational transformational leadership a critical research area. The rapid growth of publications, however, has led to fragmented knowledge, limiting a comprehensive understanding of its intellectual structure and thematic evolution. This study conducts a bibliometric analysis of 372 Scopus-indexed documents (comprising journal articles and review articles) published between 2016 and 2026, retrieved using a structured search query targeting the term “transformational leadership” in the title, abstract, and keywords fields. Using performance analysis and science mapping with VOSviewer and Microsoft Excel, the study examines publication trends, key contributors, citation patterns, collaboration networks, and conceptual structures. The results reveal a significant rise in publications, especially after 2020, peaking in 2025, indicating growing academic interest. The United States leads in contributions, followed by Indonesia and other Asian countries, reflecting increasing global participation. Thematic evolution shows a shift from traditional focuses on school effectiveness toward emerging themes such as digital transformation, artificial intelligence, teacher well-being, and sustainability. Two primary research clusters are identified through bibliographic coupling analysis using VOSviewer, with limited integration between traditional and contemporary approaches, indicating a conceptual gap. These findings highlight the need for an integrative framework that bridges classical leadership theories with digital and sustainability-oriented perspectives. A key limitation of this study is its reliance on a single database (Scopus), which may exclude relevant studies indexed elsewhere.